2019
DOI: 10.1038/s41598-019-53971-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immersive virtual reality on proximal and conditioned threat

Abstract: Virtual reality lets the user be immersed in a 3-dimensional environment, which can enhance certain emotional responses to stimuli relative to experiencing them on a flat computer screen. We here tested whether displaying two different types of threats in immersive virtual reality enhanced threat related autonomic responses measured by skin conductance responses (SCRs). We studied innate and learned threat responses because these types of threats have been shown to depend on different neural circuits in animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…Moreover, whereas postencounter contexts are associated with activation of forebrain structures, such as the vmPFC, amygdala, and hippocampus, the circa-strike context shows negative connectivity of the midbrain with these regions (26). These neural findings correspond with consistent behavioral demonstrations that increased proximity to threatening stimuli tends to amplify and maintain defensive responses, as measured via skin conductance (29,30) and startle (31), emphasizing that threat imminence also configures distinct behavioral outcomes in humans.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Moreover, whereas postencounter contexts are associated with activation of forebrain structures, such as the vmPFC, amygdala, and hippocampus, the circa-strike context shows negative connectivity of the midbrain with these regions (26). These neural findings correspond with consistent behavioral demonstrations that increased proximity to threatening stimuli tends to amplify and maintain defensive responses, as measured via skin conductance (29,30) and startle (31), emphasizing that threat imminence also configures distinct behavioral outcomes in humans.…”
supporting
confidence: 67%
“…The present experiment was designed to specifically test how spatial proximity configures differences in the initial appraisal and subsequent memory for threats, although the influence of proximity on fear conditioning may be characterized in other ways, such as temporal proximity (32). Although we paired conditioned stimuli to aversive shock, social stimuli that invade peripersonal space naturally evoke enhanced defensive responses (31), and recent evidence suggests that innate and learned threats have different behavioral consequences that might be supported by dissociable neural pathways (30). Accordingly, future studies that evaluate the influence of proximity on fear memories by considering alternative stimuli or means of associative learning, such as social mechanisms via observation (68), might aid the interpretation of the effects reported here.…”
Section: Both Cs +mentioning
confidence: 99%
“…In the non-phobic control group, the vermis was more activated with certain image formats than others. Previous results have found that the presentation of stimuli in virtual reality facilitates the response to proximal threatening stimuli [ 40 ]. The format in which visual information is presented may make a difference in neural circuits activated during the detection of nearby threats.…”
Section: Discussionmentioning
confidence: 99%
“…Shock delivery was controlled using the STM100C module connected to the STM200 constant current stimulator (BIOPAC Systems, Goleta, CA), using a unipolar pulse with a fixed duration of 67 Hz. The physical voltage was individually calibrated before the experimental task using an ascending staircase of electrical currents until shocks were rated as 'aversive' (Rosen, Kastrati, Reppling, Bergkvist, & Ahs, 2019). After finding the physical voltage that participants rated as aversive, this parameter was kept constant throughout the experiment.…”
Section: Fmri Paradigm Designmentioning
confidence: 99%